Oil Palm Seed Coating with Enriched Trichoderma asperellum (T13) to Suppress Infection of Ganoderma boninense Pat. - Gani Jawak; Eny Widajati; Endah Retno Palupi; Nutrita Toruan Mathius (Jurnal Perbenihan Tanaman Hutan, 2018)
The attack Ganoderma boninense can caused stem rot of oil palms that occur at all stage of plant growth. Trichoderma asperellum endophytic can suppressed the attack of Ganoderma in a nursery by utilizing seed coating technology. The aim of this study was to determine the best formula of seed coating materials which is compatible with T. asperellum (T13). The first experiment consisted of two phases, namely, the first phase was testing the effectiveness and compatibility of T. asperellum through a mixing technique of  T. asperellum suspension with coating material. The best three result on the first phase (25 percent arabic gum, 1 percent CMC, and 3percent arabic gum + 1 percent gypsum) were used in the second phase of the experiment, which was testing the effectiveness and compatibility of T. asperellum through soaking technique in T. asperellum suspension that continued by coating. The three best result types of formulas from the second phase (1 percent CMC, 1.5 percent CMC, and 4,5 percent arabic gum + 1,5 percent gypsum) were used for the second experiment, namely testing the resistance of oil palm seed on Ganoderma. The results show that 25 percent arabic gum, 1 percent carboxy methyl cellulose (CMC), 1 percent arabic gum + 1 percent gypsum have a potency as coating of materials. The best formula for seed coating is soaking with T. asperellum + coating 1 percent CMC, 1.5 percent  CMC and arabic gum 4.5 percent + gypsum 1.5 percent. In addition, soaking seeds with T. asperellum + coating 1.5 percent CMC can enhance the ability of seed to grow up to 16.67 percent compared to the control, but did not effective in suppressing G. boninense infection during pre-nursery stage.